Cabin Layout Optimization for Vibration Hazard Reduction in Helicopter Emergency Medical Service - Aykut Tamer; Vincenzo Muscarello; Giuseppe Quaranta; Pierangelo Masarati (Aerospace, 2020)
Helicopter Emergency and Medical Service (HEMS) vehicles require a specially configured cabin that supports the quick transport of a rescue team to the site of an emergency and return of patients back to a full capacity hospital, while sustaining the patients’ health using specifically designed, but otherwise state-of-the-art life-support equipment. The effectiveness and safety of the service may be challenged by the vibratory level, which could be improved by optimally positioning the affected subjects within the cabin. However, the bare dynamical response of the airframe can lead to erroneous evaluation of vibration performance, since pilots, crew, patients, and medical equipment dynamically interact with the helicopter through their interfaces with the structure. Therefore, layout optimization of a HEMS vehicle for low vibration requires the capability to efficiently analyze a large set of candidate coupled helicopter-interface-subject configurations, reaching a suitable trade-off between model detail and computational cost. This work presents an effective vibration rating of medical helicopters to support vibration hazard reduction by minimization of cabin interior accelerations. The tool is able to model high-fidelity rotorcraft aeroservoelasticity, easily connect formulations representing the dynamics of humans, equipment, and their interfaces, and calculate the vibration performance of the resulting coupled models. The approach is applied to a medium-weight helicopter to find its lowest vibration HEMS configuration. It is demonstrated that the optimal positioning of HEMS subjects can significantly reduce vibration hazard and improve operation safety, nearly as effectively as the application of vibration attenuation solutions with a fixed cabin layout.